Experimental analysis and WallDYN simulations of the global nitrogen migration in ASDEX Upgrade L-mode discharges. (9th February 2016) - Meisl, G.; Schmid, K.; Oberkofler, M.; Krieger, K.; Lisgo, S.W.; Aho-Mantila, L.; Reimold, F.; Lunt, T.
Abstract: This work presents ASDEX Upgrade experiments, where the nitrogen deposition and re-erosion on divertor manipulator samples and the effect of its transport through the plasma were studied. These results are compared to WallDYN-DIVIMP simulations based on SOLPS plasma backgrounds and employing an improved WallDYN model, which includes the effusion of nitrogen from saturated surfaces. On one hand, this allows the WallDYN code and the new saturation model with a comprehensive data set to be benchmarked, on the other hand the simulations help in the interpretation of the experimental results. Both, experimental results and simulations, show that the N content in the region of the outer strike line reaches its steady-state value within one discharge. The simulations also reproduce the experimentally observed nitrogen content in samples exposed to N2 -seeded discharges. With respect to the boron deposition, the nitrogen deposition in a non-seeded discharge and the re-erosion of nitrogen discrepancies to the WallDYN-DIVIMP simulations are observed. Based on SDTrimSP simulations, these are attributed to the missing depth resolution of the WallDYN surface model. A detailed comparison of spectroscopic measurements to WallDYN simulations, based on a novel synthetic spectroscopy diagnostic for WallDYN, shows that the nitrogen fluxes in the plasma are well described by the simulations. From a comparison of several WallDYN-DIVIMP simulations employing customized onion-skin model plasma backgrounds the physical processes controlling the nitrogen concentration in the core plasma and the applicability of onion-skin model plasma backgrounds are discussed. From these simulations the private flux zone with the gas valve, the outer baffle and the high field side main wall are identified as the main sources for the nitrogen content of the core plasma.